Saiba como funciona e seja feliz: estudo das modalizações dos saberes nos sites instrucionais - Santos, Thiara Ribeiro (2012)
This research is focused on the user agreements of sites specialized in instruction videos that propagate modal guides which indicate how the users-recipients of the information should be and should do in many daily tasks. The orientations on how to act are offered through recipes that instruct provide a step by step guide to complete all the requirements for successful completion of actions. This project will analyse how the sites are categorized and how the topics are organized to their readers. Beauty, health and lifestyle are examples of topics related to personal appearance, the contents to be covered in the research corpus. A map of communication devices that exist within the sites will be created and investigated, beginning from the modal arrangements of the to do and to know operated within the establishment of communication contracts, the effects of meaning that derive from the texts in order to identify the existence of modalizations and instigation of the consumption. The research questions are the following: what are the devices that fortify the communication contracts within the sites? How are the readers summoned? How is the biopolitical program proposed? How does the modalizations happen? How does the navigation of the site take place? How is organized the distribution of thematic schedules concerning the ways to donate competence to the users? Is there encouraging material consumption (indications of stores) and immaterial consumption (encouraging new skills/ knowledge) through the topics explored? The corpus consists of 14 sites: 5min, About.com, Ask, Askmen, Como fazer as coisas, Doityourself, eHow, Helpfulvideo, Howcast, MonkeySee, Saber Hacer, Videojug, Wikihow and Wonderhowto. The investigation of the most used devices will be evidenced to identify the discursive strategies of the enunciators. We also elaborate the map of the categories of the video classes that are in the sites and organizations of the arguments of this projetc based on the speeches and theories abou self-help, biopolitics, daily, hypermedia narratives, cyberspace and postmodern consumption. The theoric fundamentation includes studies about the communication speeches as Charaudeau, Deleuze, Foucault and Semprini, in the field of cyberspace the theories of Trivinho, Rifkin and Castells, and other scholars such as Bauman, Prado, Freire Filho, Certeau and Greimas